Development and current state of seawater shrimp farming, with an emphasis on integrated multi‐trophic pond aquaculture farms, in China – a review - Zhi‐Qiang Chang; Amir Neori; Yu‐Ying He; Ji‐Tao Li; Ling Qiao; Steven Ian Preston; Ping Liu; Jian Li (Reviews in Aquaculture, 2020)
Shrimp farming has been the fastest‐growing sector in seawater aquaculture and has contributed to improving the farmers income and the utilization efficiency of aquaculture resources in China. The shrimp industry has deployed ever‐improved and innovated methods, from extensive farming to semi‐intensive and intensive farming. Various high‐density intensive culture models, such as high‐land, greenhouse and indoor industrialized culture models, have been used for shrimp pond farming in the coastal area. However, efficiency, environmental and social considerations have led to an increasing adoption of the environmentally‐friendly culture model called integrated multi‐trophic aquaculture (IMTA). This has occurred most rapidly along the northern and central coasts of China. The deployed IMTA culture models reviewed here are shrimp + crab, shrimp + fish, shrimp + sea cucumber, shrimp + jellyfish + clam, shrimp + crab + clam, shrimp + crab + clam + fish and the ridgetail white shrimp polyculture in saline alkaline water, which have been tailored to local conditions and organisms' characteristics. Suitable organism varieties and the maintenance of suitable eco‐friendly water quality have been key to success. The eco‐friendly IMTA culture models described here fully exploit the pond culture resources, to increase production with minimal additional feed and labor inputs, while reducing effluent emissions and treatment cost. The performance of shrimp IMTA models is compared to shrimp monoculture models regarding the economics. An equally important outcome of this publication is making generally accessible the findings from a vast Chinese scientific literature on shrimp culture that has hitherto been unavailable in English.